Care avoidance among homeless people and access to care: an interview study among spiritual caregivers, street pastors, homeless outreach workers and formerly homeless people - Hanna T. Klop; Kirsten Evenblij; Jaap R. G. Gootjes; Anke J. E. de Veer; Bregje D. Onwuteaka-Philipsen (BMC, 2018)
Abstract Background Because of their poor health and social vulnerability, homeless people require specific care. However, due to care avoidance, homeless people are often not involved in care. This study aims to get insights into reasons for and kinds of care avoidance among homeless people and to provide suggestions to reach this target group. Methods Semi-structured individual interviews were conducted among street pastors (n = 9), spiritual caregivers (n = 9), homeless outreach workers (n = 7) and formerly homeless people (n = 3). Participants were recruited by purposive sampling in the four major cities in the Netherlands (Amsterdam, Utrecht, Rotterdam, The Hague). The verbatim transcripts were analysed using thematic analysis. Results The term care avoidance was perceived as stigmatizing. Care avoidance is found to be related to characteristics of the homeless person (e.g. having complex problems, other priorities) as well as of the system (e.g. complex system, conditions and requirements of organizations). The person-related characteristics suggestions to involve homeless persons include tailoring care and building relationships, which might even be prioritised over starting care interventions. Setting limits on behaviour without rejecting the person, and an attitude reflecting humanity, dignity and equality were also important factors in making care more accessible and lasting. As regards system-related characteristics, the suggestions include clear information and communication to homeless people who avoid care as being crucial in order to make care more accessible. Other suggestions include quiet and less busy shelters, a non-threatening attitude and treatment by professionals, self-reflection by professionals and finally a change of policy and legislation regarding available time. Conclusions Reasons for care avoidance can be found in the interplay between both the individual and the system; measures to reduce care avoidance should be taken at both levels. These measures are centred on lowering the barriers to care inter alia by incorporating building trust and understanding into the care provided.